Use the green media / Dean Pilar C Braga - Braga, Dean Pilar C (Faculty of Communication and Media Studies (FCMS), 1993)
The task of environmental protection and management is so vast that no amount of effort and investment by environmental experts and planners can be expected to achieve very much without the involvement of the media in motivating large-scale participation of the people.